If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + 3b = 19 Solving 5a + 3b = 19 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. 5a + 3b + -3b = 19 + -3b Combine like terms: 3b + -3b = 0 5a + 0 = 19 + -3b 5a = 19 + -3b Divide each side by '5'. a = 3.8 + -0.6b Simplifying a = 3.8 + -0.6b
| Y+8=-6(x-9) | | p^2+p-11=0 | | Y+8=-6x-54 | | 5x^2+15=3x^2-3 | | x+(-38)=50 | | 4-3x=44 | | Y+2.4=2.1x-3.78 | | 2x^2-4x-18=12 | | 2x^2-27x+36=0 | | 6v^2-9v-81=0 | | 2x+11=180 | | -12-x=-8 | | x^2+11x-9=-12 | | 3(n+2)+2(n-3)=5 | | 0.66n-7=19 | | 4x^2+2x-56=0 | | 3v^2+10v-45=12 | | 6(20)-10= | | 26=16+r | | 100-2y=10 | | 6b^2+b-49=8 | | x-7.1=-4.6 | | 29+x=-32 | | .5(y+2)-.3=.4y+.5 | | 1.5x+2.5x+x=25 | | 20-5y=100 | | 6p^2-6p-132=-12 | | 4N-10=30 | | 5n+2n-9=47 | | 9-2(3a+5)=4a+3(a-9) | | 3x^2+31x+36=0 | | 7x^2+23x+6=0 |